Health Education of Visual Inspection Using Acetic Acid (VIA) as Cervical Cancer Screening - Kholilah Lubis; Desti Nataria; Zilfi Yola Pitri; Mutia Felina (Ahmar Metakarya: Jurnal Pengabdian Masyarakat, 2023)
Cervical Cancer (CC) is the fourth most frequently diagnosed malignancy and the greatest cause of cancer death in women, with 24 out of every 100.000 women years (approximately 15/100.000) in Indonesia. Human Papilloma Virus is a cause that triggers the development of a pre/ invasive lesion 15-20 years after the initial infection. An Alternative screening technique that’s easily carried out by healthcare, such as Visual Inspection of Acetic Acid (VIA) was needed. The community service aims to address the community's ignorance and concern around VIA as CC screening, which will increase the community's (women) willingness and knowledge to assess reproductive health. Lecturers at Prima Nusantara Bukittinggi University collaborated with the Public Health Office in Bukittinggi and Mandiangian Koto Selayan District with questionnaires (20 questions as pre-test and post-test) in Forum Group Discussion in January 2021. The participants are married women. The result was the majority of participants were estimated 36-45 years old (46%), 18 participants were at university/ college educational level (36%), and the majority of the participants were housewives (50%). There was a significant difference (p-value = 0.000). Community service provides good benefits to increase the knowledge of married women. We hope the participants will want to participate in the VIA held at Prima Nusantara Bukittinggi University.